Acute metabolic responses to a high-carbohydrate meal in outpatients with type 2 diabetes treated with a low-carbohydrate diet: a crossover meal tolerance study - Haimoto, Hajime (BioMed Central, 2009)
BACKGROUND: A low-carbohydrate diet (LCD) achieves good glycemic control in type 2 diabetes (T2DM) compared with a high-carbohydrate diet. With respect to energy metabolism, acute metabolic responses to high-carbohydrate meals (HCMs) have not been determined in LCD patients with T2DM. SUBJECTS AND METHODS: We enrolled 31 subjects with T2DM (mean age: 62 yrs, mean hemoglobin A1c level: 6.9%), of whom 13 were on a strict LCD (26% carbohydrate diet), and 18 a moderate one (44% carbohydrate diet). Two isocaloric meals were administered to all subjects in a randomized crossover design. The carbohydrate:protein:fat ratios of HCMs and low-carbohydrate meals (LCMs) were 59:20:21 and 7:20:73, respectively. Serum β-hydroxybutyrate, acetoacetate, free fatty acids (FFAs), triglyceride and insulin, and plasma glucose concentrations were measured for 120 minutes after the intake of each meal. RESULTS: HCMs rapidly decreased postprandial β-hydroxybutyrate, acetoacetate and FFA concentrations within 2 hours in all patients in combination with rapid increases in serum insulin and plasma glucose, while LCMs increased or did not change β-hydroxybutyrate, acetoacetate and FFAs (P < 0.001 for all). HCMs did not change postprandial triglyceride concentrations over 2 hours, while LCMs gradually increased them (P < 0.001). HCMs sharply and rapidly decreased postprandial β-hydroxybutyrate and acetoacetate concentrations in strict LCD subjects over 2 hours, but only slightly decreased them in moderate LCD subjects (P < 0.001, difference between strict and moderate LCD subjects). The parameter Δketone bodies (level at 120 minutes - level at baseline) was significantly correlated with the insulinogenic index (Spearman's r = 0.503 for β-hydroxybutyrate and 0.509 for acetoacetate), but not with total insulin secretory capacity. Moreover, HCMs slightly decreased postprandial triglyceride levels in strict LCD subjects but somewhat increased them in the moderate LCD subjects (P = 0.002). The parameter Δtriglyceride was significantly correlated with background dietary %carbohydrate (Spearman's r = 0.484). CONCLUSION: HCMs rapidly decreased postprandial ketone body concentrations in T2DM patients treated with a LCD. The decreases were more remarkable in strict than in moderate LCD subjects. HCMs slightly decreased postprandial triglyceride levels in strict LCD subjects. The parameter Δketone bodies was significantly correlated with the insulinogenic index, as was Δtriglyceride with background dietary %carbohydrate.